2020
DOI: 10.1080/17450128.2020.1829228
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s difficult to help when I am not sitting next to them’: How COVID-19 school closures interrupted teachers’ care for newly arrived migrant and refugee learners in Denmark

Abstract: Teachers play a critical role in providing social and emotional support for newly arrived migrant and refugee learners. Such care ordinarily takes place in the classroom, raising questions about the impact of the 2020 COVID-19 school closures on their care work. In this article we analyze qualitative data from phone interviews with eight teachers in Danish preparatory classes, paying particular attention to the challenges they faced staying in contact with, and supporting, migrant and refugee learners during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 26 publications
1
37
0
1
Order By: Relevance
“…Thus, having to teach and communicate with the learners remotely meant that teachers could not reach all learners equally due to technical and other limitations. Primdahl et al (2020) found similar results. In the context of widespread school closures to slow the spread of COVID-19, UNESCO is now working with many ministries of education in affected and concerned countries to ensure continued learning for all children and youths through alternative channels (UNESCO, 2020b).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, having to teach and communicate with the learners remotely meant that teachers could not reach all learners equally due to technical and other limitations. Primdahl et al (2020) found similar results. In the context of widespread school closures to slow the spread of COVID-19, UNESCO is now working with many ministries of education in affected and concerned countries to ensure continued learning for all children and youths through alternative channels (UNESCO, 2020b).…”
Section: Discussionsupporting
confidence: 62%
“…A few notes were attached to each coded sound bite to remind the researcher of their content, and only sound bites deemed relevant for inclusion in this paper were transcribed. Drawing on Attride-Stirling's method ( 2001) of thematic network analysis, the researcher organized the sound bites thematically (Primdahl, et al, 2020;Attride-Stirling, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have also been raised that border closures may increase smuggling of migrants ( Sarrica et al, 2020 ). COVID-19 may meanwhile pose a barrier to integration for migrants and refugees ( Falkenhain et al, 2020 ), for example due to the suspension and modification of resettlement schemes ( Brickhill-Atkinson and Hauck, 2020 , Rush, 2020 ), and education programmes ( Brickhill-Atkinson and Hauck, 2020 , Primdahl et al, 2020 , Mupenzi et al, 2020 , OECD 2020 , Silverman et al, 2020 ). Migrants who are particularly vulnerable may be disproportionality affected by the negative social impact of lockdown ( Zero and Geary, 2020 , Sabri et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Concerns have also been raised that border closures may increase smuggling of migrants (61). COVID-19 may meanwhile pose a barrier to integration for migrants and refugees (62), for example due to the suspension and modification of resettlement schemes (63, 64), and education programmes (63, 6568). Migrants who are particularly vulnerable may be disproportionality affected by the negative social impact of lockdown (69, 70).…”
Section: Resultsmentioning
confidence: 99%